2000
DOI: 10.2105/ajph.90.2.264
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and correlates of physical activity among US women 40 years and older

Abstract: A B S T R A C TObjectives. This study describes the patterns of physical activity among minority women by using a variety of definitions and determines sociodemographic and behavioral correlates of physical activity in this population.Methods. A cross-sectional study was conducted in 1996 and 1997 among US women 40 years and older (n = 2912) of the following racial/ethnic groups: African American, American Indian/ Alaskan Native, Hispanic, and White.Results. Physical activity was lowest among African Americans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
51
3
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(67 citation statements)
references
References 34 publications
10
51
3
3
Order By: Relevance
“…Previous research conducted in Latin America showed similar results, women were less likely to participate in leisure time PA but spent more time in household activities. 29,30 We found no evidence of disparity participation in PA and sports related to traditional gender roles from Argentina, Chile or Uruguay. In occupation, women also showed a lower PA score compared to men (770 vs. 4810 MET-minutes/week, respectively) mainly at the expense of reducing manual labor activities.…”
Section: Discussionmentioning
confidence: 57%
“…Previous research conducted in Latin America showed similar results, women were less likely to participate in leisure time PA but spent more time in household activities. 29,30 We found no evidence of disparity participation in PA and sports related to traditional gender roles from Argentina, Chile or Uruguay. In occupation, women also showed a lower PA score compared to men (770 vs. 4810 MET-minutes/week, respectively) mainly at the expense of reducing manual labor activities.…”
Section: Discussionmentioning
confidence: 57%
“…323 Older Hispanic women were classified as among the least physically active groups in the country. 324,325 However, these prior studies did not account for the physical activity that occurs during normal working hours or for transportation-related physical activity. Occupational physical activity may be more important among Hispanics, because many more of them work in blue-collar than white-collar jobs, which tend to be more physically demanding.…”
Section: Prevalence Of Cvd Risk Factors In Hispanicsmentioning
confidence: 99%
“…[10][11][12] Therefore, communities with trails and individuals who use them are of great interest for better understanding the characteristics that facilitate trail use. However, the majority of studies assessing trail use have been conducted among predominately non-Hispanic White populations.…”
mentioning
confidence: 99%